Domains of Contemporary and Future Ethical Dilemmas - Hadjistavropoulos, Thomas (Canadian psychology = Psychologie canadienne, 2023)
The types of ethical dilemmas that psychologists face do not remain static but evolve with the times and as a function of technological/scientific advances, political, world and national events (e.g., pandemics, international conflicts) as well as shifts in research paradigms and in sensitivity to individual aspects of identity. The focus of this article is on domains of ethical dilemmas that have been increasingly preoccupying psychologists in recent years (e.g., internet-delivered psychological interventions, applications of social media and computer vision technologies, use of advanced brain imaging procedures in research, genetic testing in clinical settings, refugee integration, work with patient partners in research, open access publishing, and open sharing of research data). Consideration is also given to increased sensitivity to cross-cultural and individual differences that has led to changes in the way that psychologists use language and work with diverse groups. The goal of this article is to raise awareness of the manner in which ethical dilemmas and views about ethicality shift over time. It is recommended that ethics courses and related training initiatives encourage psychologists to remain mindful of emerging ethical issues and foster an understanding of the manner in which accumulating knowledge and changes in society can impact our approach to ethical decision-making. Les types de dilemmes éthiques auxquels les psychologues sont confrontés ne restent pas statiques, mais évoluent avec le temps et en fonction des avancées technologiques/scientifiques, des événements politiques, mondiaux et nationaux (par exemple, les pandémies, les conflits internationaux) ainsi que des changements dans les paradigmes de recherche et dans la sensibilité aux aspects individuels de l'identité. Cet article se penche sur les domaines de dilemmes éthiques qui préoccupent de plus en plus les psychologues ces dernières années (par exemple, les interventions psychologiques délivrées par Internet, les applications des médias sociaux et des technologies de vision par ordinateur, l'utilisation de procédures avancées d'imagerie cérébrale dans la recherche, les tests génétiques en milieu clinique, l'intégration des réfugiés, le travail avec des patients partenaires dans la recherche, la publication en libre accès et le partage ouvert des données de recherche). L'on tient également compte de la sensibilité accrue aux différences interculturelles et individuelles qui a conduit à des changements dans la façon dont les psychologues utilisent le langage et travaillent avec des groupes divers. Le but de cet article est de sensibiliser par rapport à la manière dont les dilemmes éthiques et les points de vue sur l'éthique évoluent. Il est recommandé que les cours d'éthique et les initiatives de formation connexes encouragent les psychologues à rester attentifs aux questions éthiques émergentes et à favoriser la compréhension de la manière dont l'accumulation des connaissances et les changements dans la société peuvent avoir un impact sur notre approche de la prise de décision éthique. Public Significance Statement The types of ethical dilemmas that psychologists face evolve with the times as a function of a variety of factors such as technological advances and increases in knowledge. Psychologists must remain mindful of emerging ethical issues and the way in which changes in society can impact our approach to ethical decision-making.